2004
DOI: 10.1001/jama.291.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and Clinical Features of Enterovirus 71 Infections in Household Contacts in Taiwan

Abstract: UTBREAKS OF ENTEROVIrus 71 have been documented since it was recognized in California in 1969. 1 Fatalities in adults and children have been reported in Bulgaria, Hungary, and Malaysia. 2-4 The largest and most severe enterovirus 71 epidemic occurred in Taiwan in 1998. 5-10 The clinical syndromes and severity of cases were diverse. Thousands of cases of hand, foot, and mouth disease (HFMD) and herpangina occurred, 405 experienced severe neurological complications, such as encephalitis, meningitis, poliolike sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
161
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(172 citation statements)
references
References 21 publications
7
161
2
2
Order By: Relevance
“…Deterministic models for HFMD have been discussed by many researchers, but such models mainly considered the direct transmission rate although there is evidence showing that recessive subpopulation can infect others and so should not be neglected (Ma et al, 2013;Chang et al, 2004). Hence, in our model the infected individuals are divided into two subgroups (symptomatic and asymptomatic).…”
Section: Discussionmentioning
confidence: 99%
“…Deterministic models for HFMD have been discussed by many researchers, but such models mainly considered the direct transmission rate although there is evidence showing that recessive subpopulation can infect others and so should not be neglected (Ma et al, 2013;Chang et al, 2004). Hence, in our model the infected individuals are divided into two subgroups (symptomatic and asymptomatic).…”
Section: Discussionmentioning
confidence: 99%
“…Patient one had classic risk factors for enteroviral infection, in particular, exposure to ill household contacts, including an infant in diapers [10]. His initial clinical presentation, including the associated gastrointestinal symptoms, was also typical.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a frequent occurrence of CD4-dependent RdRp-specific T-cell responses in healthy adults, suggesting a potentially protective role of these responses, which may partially explain the asymptomatic and mild disease outcomes in adults who were previously exposed/infected with EV71. 39,40 It is reported that enterovirus infections occur frequently in infancy and induce T-cell immunity. 41 Cellular immunity is suggested to be a more sensitive indicator of neonatal enterovirus infections than antibodies.…”
Section: Discussionmentioning
confidence: 99%